(untitled) (Revista Ciência Agronômica, 2020)
Knowledge on nitrogen (N) utilization efficiency in colored cotton enables the correct management of N fertilizers, optimizing yield and minimizing environmental degradation.The objective of this study was to evaluate the N utilization efficiency and to determine the accumulation of dry matter and N by naturally colored cotton cultivars subjected to N fertilization in the Brazilian semi-arid region.The experiment was carried out under field conditions, at the Farm of the Federal Rural University of the Semi-Arid, in 2016 and 2017. The experimental design was in randomized blocks with split plots and four replicates, randomizing five N doses (0; 50; 100; 150 and 200 kg ha-1) in the main plot and four colored cotton cultivars (BRS Safira, BRS Rubi, BRS Topázio and BRS Verde) in the subplots. Dry matter and N accumulations, agronomic, recovery, agrophysiological and physiological efficiencies in N utilization, and harvest index were evaluated. Cotton accumulates around 130 kg ha-1 of N along its cycle and directs 56.3% to seeds, 29% to leaves, 10.6% to stem and 3.8% to fibers. Nitrogen agronomic efficiency and recovery efficiency decrease with increased N doses. The cultivar BRS Topázio is the most responsive to N fertilization and the cultivar BRS Verde is the least responsive.